A medical nonwoven adhesive and preparation method thereof
By using amphiphilic macromolecular RAFT reagent and RAFT emulsion polymerization technology, a polystyrene-b-acrylate-b-poly(methyl methacrylate-free crosslinked monomer) triblock copolymer adhesive without anionic emulsifier and analgesic-free polystyrene-b-acrylate-b-poly(methyl methacrylate-free crosslinked monomer) is prepared, which solves the problems of insufficient cytotoxicity and performance of existing non-woven adhesives, and achieves a high-performance, non-cytotoxic medical non-woven adhesive.
Patent Information
- Application Number
- CN202411921784.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Existing non-woven adhesives have cytotoxic problems in medical applications, and their body strength and bonding properties are insufficient, which cannot meet the requirements of medical environments such as high temperature sterilization.
An anionic emulsifier, an anionic emulsifier, a polystyrene-b-acrylate-b-poly(methyl methacrylate-free crosslinked monomer) triblock copolymer adhesive was prepared by RAFT emulsion polymerization technology to improve the body strength and bonding properties of the adhesive.
It realizes a non-cytotoxic medical non-woven adhesive, improves the body strength, bonding performance and heat resistance of the adhesive, and meets the medical industry's demand for high-performance non-woven adhesives.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a medical non-woven fabric adhesive and a preparation method thereof. Background Art
[0002] As a kind of non-woven fabric, non-woven fabric is rich in colors and has a wide range of applications in many fields such as medical care, hygiene, and industry. In order to improve the strength and durability of non-woven fabrics, adhesives are usually used to bond them together. However, traditional non-woven adhesives often contain anionic emulsifiers, free formaldehyde and other substances, which are toxic to human cells, limiting the application of non-woven fabrics in the medical industry. Existing non-woven adhesives are basically anionic or non-ionic systems. The small molecule anionic emulsifiers therein are easy to migrate and produce cytotoxicity. Although non-ionic emulsifiers have low cytotoxicity, their emulsion stability is poor, resulting in the inability of existing non-woven adhesives to meet the needs of the medical industry.
[0003] Reversible addition-fragmentation chain transfer (RAFT) polymerization has the advantages of a wide range of applicable monomers and low reaction requirements, and is particularly suitable for the preparation of block copolymers, including polyacrylate adhesives. Patent CN 114133500 A uses an amphiphilic macromolecular RAFT agent as a chain transfer agent and the only emulsifier for the RAFT polymerization reaction, and synthesizes a polyacrylate latex with a triblock structure of poly(styrene-co-methyl methacrylate-b-acrylate-b-styrene-co-methyl methacrylate) through RAFT polymerization. The emulsion does not contain anionic emulsifiers or free formaldehyde. However, when this emulsion is used as a non-woven fabric adhesive, it still has the problems of insufficient bulk strength and poor bonding performance, resulting in insufficient performance of the prepared non-woven fabric.
[0004] Therefore, it is necessary to develop a non-cytotoxic nonwoven adhesive while improving its bulk strength, bonding properties and heat resistance to meet the requirements of medical environments such as high-temperature sterilization. Summary of the invention
[0005] In order to overcome the problems of poor body strength and low bonding performance of polyacrylate non-woven fabric adhesives in the prior art, the present invention provides a medical non-woven fabric adhesive and a preparation method thereof. The adhesive is not only non-toxic to human cells, but also can improve the bonding performance and body strength of the non-woven fabric while having good heat resistance to meet the requirements of medical environments such as high-temperature sterilization.
[0006] The technical solution adopted by the present invention is: the medical non-woven fabric adhesive is an emulsion obtained by polymerization of styrene, acrylate, methyl methacrylate and aldehyde-free cross-linking monomer as raw materials under the action of a macromolecular RAFT agent; the emulsion is a polystyrene-b-polyacrylate-b-poly(methyl methacrylate-aldehyde-free cross-linking monomer) triblock copolymer.
[0007] The present invention adopts an amphiphilic macromolecular RAFT agent as the only emulsifier, and utilizes RAFT emulsion polymerization technology to prepare an anionic emulsifier-free, aldehyde-free non-woven fabric adhesive. Through this method, the toxicity of anionic emulsifiers and free formaldehyde in traditional adhesives to human cells can be effectively avoided, thereby meeting the demand of the medical industry for non-cytotoxic adhesives. Further, RAFT polymerization technology allows precise control of the molecular weight and structure of the polymer, so that the performance of the adhesive is optimized. In the present invention, the prepared adhesive has a styrene-butyl acrylate-methyl methacrylate / cross-linking monomer triblock structure. This ABC-type structural design utilizes the advantages of RAFT polymerization technology, and the incompatibility caused by the different chemical affinity and repulsion between different blocks in the block copolymer causes different blocks to separate naturally and form different microscopic phase regions, and the nanoscale phase regions produced by microphase separation form physical crosslinking points, thereby improving the bulk strength of the adhesive. In addition, the present invention also adds a suitable formaldehyde-free cross-linking monomer in the third block, further enhancing the adhesive's bonding force to the fiber and heat resistance, which is crucial for medical non-woven fabrics that need to be sterilized in a high temperature environment, ensuring the reliability and durability of the adhesive in medical applications. In summary, the RAFT adhesive of the styrene-butyl acrylate-methyl methacrylate / cross-linking monomer tri-block structure prepared by the present invention has a microphase separation of the block structure that not only improves the adhesive's bonding performance and bulk strength, but also significantly improves its heat resistance, meeting the medical industry's demand for high-performance and non-cytotoxic non-woven adhesives.
[0008] Preferably, the raw material composition is, by weight: 10-15 parts of styrene, 15-20 parts of acrylate, 5-10 parts of methyl methacrylate, 2-5 parts of aldehyde-free crosslinking monomer, and 0.5-2 parts of macromolecular RAFT agent.
[0009] Preferably, the structural formula of the polystyrene-b-polybutyl acrylate-b-poly(methyl methacrylate-aldehyde-free crosslinking monomer) triblock copolymer is: n1 -b-nA n2 -b-(M-MMA) n3 -X; where
[0010] X is derived from the dithioester group or trithioester group of the macromolecular RAFT agent, preferably an alkyl dithioester group or an alkyl trithioester group;
[0011] R is derived from the leaving group of the macromolecular RAFT agent, preferably one of isopropanoic acid, acetic acid, 2-nitroacetic acid, and 2-aminoacetic acid;
[0012] St is a styrene monomer unit, n1 is the average degree of polymerization of the polymer chain segment, n1 = 10-5000;
[0013] nA is an acrylate monomer unit, n2 is the average degree of polymerization of the nA polymer chain segment, n2 = 10-10000;
[0014] (M-MMA) is a random copolymer of methyl methacrylate and an aldehyde-free crosslinking monomer, n3 is the average degree of polymerization of the random copolymer of (M-MMA), n3=10-5000.
[0015] Preferably, the acrylate is one of ethyl acrylate, butyl acrylate and isooctyl acrylate. Experiments have shown that the adhesive prepared using butyl acrylate has the best body strength. In addition, methyl acrylate, ethyl acrylate and isooctyl acrylate can all be used to prepare the adhesive.
[0016] Preferably, the aldehyde-free crosslinking monomer is one of N-n-butoxymethyl acrylamide, N-(isobutoxymethyl) acrylamide, diacetone acrylamide, 1,3-butylene diamine methacrylamide, and acetoacetoxyethyl methacrylate, and more preferably N-n-butoxymethyl acrylamide.
[0017] Preferably, the raw material contains A parts of styrene, B parts of methyl methacrylate and formaldehyde-free crosslinking monomer in total, calculated by mass; the ratio of A to B is between 2:3 and 3:2.
[0018] Preferably, the macromolecular RAFT agent is selected from amphiphilic macromolecular RAFT agents, such as polyacrylic acid-polystyrene RAFT agents (PAA m -PSt n -RAFT), in which the polymerization degrees m and n of polyacrylic acid and polystyrene can be adaptively adjusted.
[0019] The present invention also provides a method for preparing the medical non-woven fabric adhesive, comprising: dissolving a macromolecular RAFT agent in water, adding the macromolecular RAFT agent into a reactor together with styrene, stirring and mixing, passing nitrogen gas until the air is completely replaced, heating to 70-80°C, adding a water-soluble initiator, initiating polymerization for 60-90 minutes, then adding an aqueous solution of alkali and acrylate, polymerizing for 120-150 minutes, then adding methyl methacrylate and an aldehyde-free cross-linking monomer, polymerizing for 90-120 minutes, and post-treating the reaction solution to obtain the medical non-woven fabric adhesive.
[0020] Preferably, the post-treatment comprises: cooling to 45-60°C, adding an oxidant, slowly dripping a reducing agent aqueous solution, controlling the dripping to be completed over 15-30 minutes, and then polymerizing for 30-60 minutes to obtain the medical non-woven fabric adhesive. The post-treatment step can effectively improve the monomer conversion rate, reduce the residual monomers in the product, and avoid cytotoxicity.
[0021] Preferably, the oxidant is selected from tert-butyl hydroperoxide; the reducing agent is selected from disodium glycolate sulfinate, dithiothreitol, dithioerythritol, and tri-(2-formylethyl)phosphine hydrochloride.
[0022] Preferably, the water-soluble initiator is one of persulfate, hydrogen peroxide and their derivatives.
[0023] Preferably, the alkali is one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.
[0024] Beneficial effects of the invention: The invention provides a medical non-woven fabric adhesive with a three-block structure, wherein the first block is styrene, the second block is butyl acrylate, and the third block is a random copolymer of methyl methacrylate and an aldehyde-free cross-linking monomer. This structural design is intended to improve the bulk strength of the adhesive through microphase separation, while the introduction of the aldehyde-free cross-linking monomer enhances the adhesive's bonding properties and heat resistance to meet the application requirements of medical non-woven fabrics in a high-temperature sterilization environment. DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. In the embodiments of the present invention, the methods used are all conventional methods unless otherwise specified, and the reagents used can be obtained from commercial sources.
[0026] The chemical structure of the macromolecular RAFT agent used in the embodiment of the present invention is:
[0027]
[0028] Optionally, other commonly used amphiphilic macromolecular RAFT agents can also be used in the present invention, such as amphiphilic polymethacrylic acid-b-polymethyl methacrylate macromolecular RAFT agent (PMAA-b-PMMA-RAFT), amphiphilic polyacrylic acid-b-polystyrene macromolecular RAFT agent (AA-bS-RAFT), etc.
[0029] Example 1
[0030] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene was added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added, and 5g of ammonia water was added after initiating polymerization for 90 minutes. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes, and then 2.4g of N-n-butoxymethyl acrylamide and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes, and the polymerization reaction was continued for 60 minutes to obtain the medical non-woven fabric adhesive A having a triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0031] Example 2
[0032] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added, and 5g of ammonia water was added after initiating polymerization for 90 minutes. After 1 hour, 13.6g of butyl acrylate was added, and polymerization was carried out for 120 minutes, and then 2.4g of N-n-butoxymethyl acrylamide and 6.4g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes, and the polymerization reaction was continued for 60 minutes to obtain the medical non-woven fabric adhesive B having a triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0033] Example 3
[0034] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 12g of styrene was added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 8g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 2.4g of N-n-butoxymethyl acrylamide and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive C having the triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0035] Example 4
[0036] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 4g of N-n-butoxymethyl acrylamide and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive D having the triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0037] Example 5
[0038] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added, and 5g of ammonia water was added after initiating polymerization for 90 minutes. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes, and then 1.6g of N-n-butoxymethyl acrylamide and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes, and the polymerization reaction was continued for 60 minutes to obtain the adhesive E having a triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0039] Example 6
[0040] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiation of polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 2.4g of ethyl methacrylate and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive F having a triblock structure of styrene-butyl acrylate-methyl methacrylate / ethyl methacrylate acetoacetate.
[0041] Comparative Example 1
[0042] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 16g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 2.4g of N-n-butoxymethyl acrylamide and 4g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive G having a triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0043] Comparative Example 2
[0044] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 8g of styrene was added and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive H having a styrene-butyl acrylate-styrene triblock structure.
[0045] Comparative Example 3
[0046] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 4g of styrene was added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 16g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 2.4g of N-n-butoxymethyl acrylamide and 8g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive I having the triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide.
[0047] Comparative Example 4
[0048] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of methyl methacrylate were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 12g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then 8g of methyl methacrylate was added and polymerization was carried out for 1.5 hours to obtain. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive J having a triblock structure of methyl methacrylate-butyl acrylate-methyl methacrylate.
[0049] Comparative Example 5
[0050] 1.2g of macromolecular RAFT agent was dissolved in 4.8g of water, and 8g of styrene were added to the reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C, and then 0.05g of water-soluble initiator was added. After initiating polymerization for 90 minutes, 5g of ammonia water was added. After 1 hour, 12g of butyl acrylate was added as the second-stage monomer, and polymerization was carried out for 120 minutes. Then 8g of methyl methacrylate was added and polymerization was carried out for 1.5 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain the adhesive K having a triblock structure of styrene-butyl acrylate-methyl methacrylate.
[0051] Comparative Example 6
[0052] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 8 g of styrene was added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C, and 0.05 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 5 g of ammonia water was added. After 1 hour, 12 g of butyl acrylate was added, and polymerization was carried out for 120 minutes. Then, 2.4 g of N-n-butoxymethyl acrylamide and 8 g of methyl methacrylate were added, and polymerization was carried out for 1.5 hours. Without post-treatment, the medical non-woven fabric adhesive A1 having a triblock structure of styrene-butyl acrylate-methyl methacrylate / N-n-butoxymethyl acrylamide was obtained.
[0053]
Performance test
[0054] The prepared adhesive AK was subjected to MTT cytotoxicity test, bulk tensile strength and bulk modulus test, and the test results are shown in Table 1.
[0055] Non-woven fabrics AK were produced by a padding method using the adhesive AK obtained in Examples 1-6 and Comparative Examples 1-5, respectively. The non-woven fabrics AK were subjected to formaldehyde content determination (according to GB18401-2001-Definition of formaldehyde content in textiles), thermal shrinkage test (tested using FZ / T 50004-2011 polyester staple fiber dry heat shrinkage test method), and soap washing color fastness test (tested according to GB / T 3921-2008 Textiles - Color fastness to soap washing). The test results are shown in Table 1.
[0056] Table 1. Test results
[0057]
[0058] Note: Formaldehyde content less than 16PPM is recorded as undetectable; high temperature yellowing test conditions are 190℃ 3 minutes; soap washing color fastness is 1-5 levels, 5 is the best, 1 is the worst.
[0059] As can be seen from Table 1, compared with the ABA triblock adhesives of Comparative Example 2 (styrene-butyl acrylate-styrene) and Comparative Example 4 (methyl methacrylate-butyl acrylate-methyl methacrylate), the ABC triblock adhesive of styrene-butyl acrylate-methyl methacrylate / cross-linking monomer provided in the embodiment of the present invention has a stronger microphase separation effect, and the resulting nanoscale phase region increases the surface area of the adhesive, thereby improving the contact and adhesion with the non-woven fabric, while maintaining excellent bulk strength, so that the non-woven fabric is not easy to tear or break when subjected to external force. In Examples 1-2 and Comparative Example 1, the amount of methyl methacrylate added is different. By comparison, it can be found that the increase in the amount of methyl methacrylate added can effectively promote the bulk strength of the adhesive. In Examples 1, 3 and Comparative Example 3, the amount of styrene added is different, and the bulk strength of the adhesive shows a trend of first increasing and then decreasing with the increase in the amount of styrene added. When the amount of styrene added is 10 parts by mass, the adhesive has a relatively optimal performance. The addition amount of the aldehyde-free cross-linking monomer in Examples 1, 4, 5 and Comparative Example 5 is different. The bulk strength of the adhesive and the soap color fastness of the non-woven fabric obtained increase first and then decrease with the increase of the addition amount of the aldehyde-free cross-linking monomer N-n-butoxymethyl acrylamide. When the addition amount of N-n-butoxymethyl acrylamide is 3 parts by mass, the adhesive has a relatively optimal performance. Under this ratio, Example 6 uses an equal amount of acetoacetoxyethyl methacrylate as an aldehyde-free cross-linking monomer, and the obtained adhesive also has better performance. And Comparative Examples 2, 4, and 5 also illustrate that the addition of aldehyde-free cross-linking monomers can further improve the cross-linking degree of the adhesive film, thereby improving its bonding performance and heat resistance, and the soap color fastness of the obtained non-woven fabric is also improved accordingly, thereby ensuring the reliability and durability of the non-woven adhesive in medical applications. Compared with Example 1, Comparative Example 6 omits the post-processing step, and the obtained adhesive A1 fails to pass the cytotoxicity test. After the residual monomer detection of the product of Comparative Example 6, it is found that adhesive A1 has more residual monomers than adhesive A, thereby generating cytotoxicity. Therefore, during the preparation process, post-treatment of the reaction solution with an oxidant / reducing agent can effectively improve the conversion rate of the monomer and avoid the cytotoxicity of the residual monomer.
Claims
1. A medical nonwoven adhesive, characterized in that: The medical non-woven fabric adhesive is an emulsion obtained by using styrene, acrylate, methyl methacrylate and aldehyde-free cross-linking monomer as raw materials, polymerizing under the action of a macromolecular RAFT agent and then post-treating the reaction solution with an oxidant and a reducing agent; The emulsion is: polystyrene-b-polyacrylate-b-poly(methyl methacrylate-aldehyde-free crosslinking monomer) triblock copolymer; The raw materials include, by weight: 10-15 parts of styrene, 15-20 parts of acrylate, 5-10 parts of methyl methacrylate, 2-5 parts of aldehyde-free crosslinking monomer, and 0.5-2 parts of macromolecular RAFT agent; The raw material contains A parts of styrene, B parts of methyl methacrylate and formaldehyde-free crosslinking monomer in total, in parts by mass; the ratio of A to B is between 2:3 and 1.25 and is not 1.25; The aldehyde-free cross-linking monomer is one of N-n-butoxymethyl acrylamide, N-(isobutoxymethyl) acrylamide, diacetone acrylamide, and acetoacetoxyethyl methacrylate.
2. The medical nonwoven adhesive according to claim 1, characterized in that: The structural formula of the polystyrene-b-polyacrylate-b-poly(methyl methacrylate-aldehyde-free crosslinking monomer) triblock copolymer is: R-St n1 -b-nA n2 -b-(M-MMA) n3 -X; in, X is derived from the dithioester group or trithioester group of the macromolecular RAFT agent; R comes from the leaving group of the macromolecular RAFT agent; St is a styrene monomer unit, n1 is the average degree of polymerization of the polymer chain segment, n1 = 10-5000; nA is an acrylate monomer unit, n2 is the average degree of polymerization of the nA polymer chain segment, n2 = 10-10000; (M-MMA) is a random copolymer of methyl methacrylate and an aldehyde-free crosslinking monomer, n3 is the average degree of polymerization of the random copolymer of (M-MMA), and n3=10-5000.
3. The medical nonwoven adhesive according to claim 1, characterized in that: The acrylic acid ester is one of ethyl acrylate, butyl acrylate and isooctyl acrylate.
4. A method for preparing the medical nonwoven adhesive according to any one of claims 1 to 3, characterized in that: include: The macromolecular RAFT agent is dissolved in water, added into a reactor together with styrene, stirred and mixed, nitrogen is introduced until the air is completely replaced, the temperature is raised to 70-80°C, a water-soluble initiator is added, and after initiating polymerization for 60-90 minutes, an aqueous solution of alkali and acrylate are added, and polymerization is carried out for 120-150 minutes, methyl methacrylate and aldehyde-free cross-linking monomer are added, and polymerization is carried out for 90-120 minutes, and the reaction solution is post-treated with an oxidant and a reducing agent to obtain the medical non-woven fabric adhesive.
5. The method according to claim 4, characterized in that The post-treatment includes: adding an oxidant aqueous solution after the reaction solution is cooled to 45-60° C., then slowly dripping an aqueous solution of a reducing agent, controlling the dripping to be completed over 15-30 minutes, and then polymerizing for 30-60 minutes to obtain the medical non-woven fabric adhesive.
6. The method according to claim 5, characterized in that The oxidant is selected from tert-butyl hydroperoxide; the reducing agent is selected from one of disodium glycolate sulfinate, dithiothreitol, dithioerythritol, and tri-(2-formylethyl)phosphine hydrochloride.
7. The method according to claim 4, characterized in that The water-soluble initiator is one of persulfate and hydrogen peroxide.
Citation Information
Patent Citations
Triblock copolymer tough resin latex and preparation method thereof
CN114133500A
Burn-out printing flock fabric and preparation thereof
CN101476246A
Method for preparing super-hydrophobic coating through water-based RAFT miniemulsion polymerization
CN112375450A